Transcriptome and hormone metabolome reveal the mechanism of stem bending in water lily (Nymphaea tetragona) cut-flowers - Li, Jie; Sheng, Yuhui; Xu, Huixian; Li, Qinxue; Lin, Xiuya; Zhou, Yang; Zhao, Ying; Song, Xiqiang; Wang, Jian (Frontiers in Plant Science, 2023)
Water lilies are popular ornamental cut-flowers with significant economic and cultural value.However, stem bending affects the preservation of cut-flowers during their vase life. To gain further insights into the molecular mechanisms of stem bending, transcriptome profiling, hormone measurement, and morphological analysis were performed using the stems of the 'Blue Bird' water lily. Transcriptome analysis revealed that 607 differentially expressed genes (DEGs) were associated with the dorsal and ventral stems of the water lily, of which 247 were upregulated and 360 were down-regulated. Significant differences in genes associated with plant hormones, calcium ions, glucose metabolism, and photosynthesis pathways genes involved in the dorsal and ventral areas of the curved stem. In particular, DEGs were associated with the hormone synthesis, gravity response, starch granules, Ca 2+ ions, and photosynthesis. The results of qRT-PCR were consistent with that of the transcriptome sequence analysis. A total of 12 hormones were detected, of which abscisic acid, indole-3-carboxaldehyde, indole-3-carboxaldehyde and jasmonic acid were significantly differentially expressed in the dorsal and ventral stems, and were significantly higher in the dorsal stem than in the ventral stem. The cell morphology in the dorsal and ventral areas of the curved stem clearly changed during vase life. The direction of starch granule settlement was consistent with the bending direction of the water lily stem, as well as the direction of gravity. In conclusion, stem bending in water lily cut-flowers is regulated by multiple factors and genes. This study provides an important theoretical basis for understanding the complex regulatory mechanism of water lily stem bending.